The correlation between nursing students' healthy lifestyle behaviors, cardiovascular disease risk factors' knowledge level, and obsession symptoms - Dilek Baykal; Leman Kutlu; Burcu D Demir (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Nursing students have a role in the awareness of risk factors in the development of healthy lifestyle behaviors. Nursing students' awareness of disease risk factors plays a role in developing healthy lifestyle behaviors. Therefore, it was aimed to determine the relationship between the effect of nursing students' healthy lifestyle behaviors and cardiovascular disease risk factors' knowledge levels and obsessive-compulsive symptoms. MATERIALS AND METHODS: This was a descriptive cross-sectional study. Two hundred and twenty-four students studying in the nursing departments of two foundation universities participated in the study between April and October 2020. Sociodemographic information form, Health Promoting Lifestyle Profile II (HPLP-II), Cardiovascular Disease Risk Factors Knowledge Level (CARRF-KL), and Maudsley Obsessive-Compulsive Inventory (MOCI) were applied to the students. RESULTS: It was found that the nursing students' healthy lifestyle behaviors (123.53 ± 25.78) and cardiovascular risk factors' knowledge level (21.08 ±± 2.70) were high. Obsessive-compulsive symptoms (16.12 ± 6.22) were moderate. In the correlation of sociodemographic characteristics, it was found that age correlated with the nutrition subdimension of CARRF-KL and HPLP-II, income level correlated with HPLP-II, place of residence correlated with HPLP-II, CARRF-KL, and MOCI, and having a health problem correlated with health responsibility. Income status, place of residence, and presence of health problems were found to be correlated with HPLP-II in all subdimensions in the regression analysis. In the regression analysis of HPLP-II with CARRF-KL and MOCI scales, it was found that it was significantly related to interpersonal relations, spiritual growth, stress management, and total score dimensions. CONCLUSION: Healthy lifestyle behaviors of nursing students are related to cardiovascular risk factors' knowledge level and obsession symptoms. In addition, some demographic characteristics affect healthy lifestyle behaviors.